Prognostic role of STAT6 in patients with non-small cell lung cancer - O. Vynnychenko; Y. Moskalenko; O. Yazykov; I. Tymchenko; O. Seleznov; O. Sulaieva; R. Moskalenko (Regulatory Mechanisms in Biosystems, 2024)
Lung cancer is the leading cause of death from cancer in Ukraine and worldwide. The impact on the tumor microenvironment is the most promising direction for lung cancer therapy. Tumor-associated macrophages of type M2 have the most powerful immunosuppressive properties. A new potential way of influencing M2 macrophages is the signaling protein and activator of transcription 6 (STAT6). The aim of our study was to evaluate the role of STAT6 in the formation of the immunosuppressive microenvironment and the prognosis of patients with radically treated non-small cell lung cancer (NSCLC). We performed an immunohistochemical examination of the tumor tissue of 42 NSCLC patients with antibodies to CD8+, forkhead box P3 (FOXP3+), CD163+, and STAT6. The impact on survival was assessed by Cox regression analysis. The median follow-up period for the studied cohort was 57.9 ± 4.2 months. 50.0% of patients with NSCLC have high expression of STAT6. We established that STAT6 correlates with the histology of NSCLC and the gender of patients. High expression of STAT6 is significantly more determined in squamous cell carcinomas than in adenocarcinomas. In patients with squamous cell carcinomas, metastasis to regional lymph nodes is associated with an immune exclusion phenotype and is mediated by a high infiltration of tumor stroma M2 macrophages. An inflammatory immune phenotype with low CD163+, FOXP3+, and STAT6 expression is most typical for adenocarcinoma. Low STAT6 and an inflammatory immune phenotype are more common in women; high STAT6 and an immune exclusion phenotype in men. Females and patients with high CD8+ expression in tumor clusters, low CD163+ in tumor stroma, and low STAT6 expression have better overall survival. Conclusions: STAT6 overexpression is associated with immunosuppressive microenvironment and has a negative impact on recurrence-free survival and overall survival in NSCLC patients. To obtain more accurate results, it is necessary to conduct a study that includes a larger cohort of patients, in particular, female patients.